Volatility Spillovers among the Cryptocurrency Time Series - Zouheir Mighri; Majid Ibrahim Alsaggaf (International Journal of Economics and Financial Issues, 2019)
This paper uses different multivariate GARCH models to model conditional correlations and analyze the volatility spillovers between cryptocurrency time series. The dynamic conditional correlation GARCH model is found to fit the data the best. Our empirical results are fourfold. First, on average, a $1 long position in BitShares (BTS) can be hedged for 15% with a short position in MonaCoin (MONA), while a $1 long position in MONA can be hedged for 14% with a short position in Ripple (XRP). Second, the average weight for the BTS/MONA portfolio is 0.48, indicating that for a $1 portfolio, 48% should be invested in BTS and 52% invested in MONA. Third, the average weight for the BTS/XRP portfolio indicates that 27% should be invested in BTS and 73 % invested in XRP. Finally, the average weight for the MONA/XRP portfolio indicates that 33% should be invested in MONA and 67% invested in XRP. Keywords: Cryptocurrencies, Multivariate GARCH, Volatility spillover, Hedging, Portfolio designs. JEL Classifications: C5, C22, C32, G1. DOI: https://doi.org/10.32479/ijefi.7383